From Localized Scleroderma to Systemic Sclerosis: Coexistence or Possible Evolution - Giuggioli Dilia; Colaci Michele; Cocchiara Emanuele; Spinella Amelia; Lumetti Federica; Ferri Clodoveo (Hindawi Limited, 2018)
Background. Systemic sclerosis (SSc) and localized scleroderma (LoS) are two different diseases that may share some features. We evaluated the relationship between SSc and LoS in our case series of SSc patients. Methods. We analysed the clinical records of 330 SSc patients, in order to find the eventual occurrence of both the two diseases. Results. Eight (2.4%) female patients presented both the two diagnoses in their clinical histories. Six developed LoS prior to SSc; in 4/6 cases, the presence of autoantibodies was observed before SSc diagnosis. Overall, the median time interval between LoS and SSc diagnosis was 18 (range 0-156) months. Conclusions. LoS and SSc are two distinct clinical entities that may coexist. Moreover, as anecdotally reported in pediatric populations, we suggested the possible development of SSc in adult patients with LoS, particularly in presence of Raynaud's phenomenon or antinuclear antibodies before the SSc onset.